선박 추진축의 선회임계속도에 관한 연구 - 김용철(Yong Chul Kim); 이건도(Gun Do Lee) (大韓造船學會 論文集, 1994)
In this paper the modelling procedure and analysis technique for the prediction of accurate critical speeds of marine propeller shafts are suggested. As a solution method the transfer matrix method is employed to calculate the critical speeds, which are correspond to natural frequencies of the shaft in lateral vibration, and whirling responses. Furthermore, in order to check the validity of the simple prediction formulae, such as Jasper's formula and Panagopulos's formula, numerical calculations were performed. From the numerical results it was found that the critical speed of the propeller shaft is sensitive to the position and the supporting conditions of journal bearings. 본 논문에서는 선박 추진축계의 정확한 임계속도 추정을 위한 모델링방법 및 해석방법을 제시하였다. 해석방법으로서는 전달행렬법을 사용하여 추진축의 임계속도 및 선회운동응답을 구하였다. 또한, Jasper식과 Panagopulos식 등과 같은 간이 추정식들의 타당성을 검증하기 위하여 수치계산을 수행하였다. 일반적인 선박 추진축계에 대한 수치계산 결과로부터 축의 임계속도는 저어널베어링의 위치 및 지지조건에 민감함을 알 수 있었다.